Cursos online de especialização na estrutura da pós-graduação no Brasil - Marcelo Pupim Gozzi; Vani Moreira Kenski (EccoS – Revista Científica)
At the beginning of the implementation of graduate courses in Brazil, those who were interested in the academic area, or who wished to become researchers and university professors, decided to continue their process of higher education. They sought the graduate courses stricto sensu level and thus established their training as masters and doctors. Today, the training never ends with the completion of an undergraduate course. It needs a permanent process of update. This context has fueled the demand for specialized courses at graduate courses. Upon the increase of the supply of these courses,this article aims to discuss the context of specialization courses in Brazil, especially those offered online in distance education mode. It was possible to see that, on one hand, professionals are realizing the need for continuing education and distance education has the facilities and benefits of f lexible space-time, on the other hand, this expansion requires that more teachers are trained to work in these courses.